2019
DOI: 10.3390/w11102145
|View full text |Cite
|
Sign up to set email alerts
|

Application of Asymmetrical Statistical Distributions for 1D Simulation of Solute Transport in Streams

Abstract: Analytical solutions of the one-dimensional (1D) advection–dispersion equations, describing the substance transport in streams, are often used because of their simplicity and computational speed. Practical computations, however, clearly show the limits and the inaccuracies of this approach. These are especially visible in cases where the streams deform concentration distribution of the transported substance due to hydraulic and morphological conditions, e.g., by transient storage zones (dead zones), vegetation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Because of this, we used in our research also alternative formulation of the onedimensional analytic solution of the ADE based on the assumption of asymmetrical substance spreading. This alternative solution is based on the Gumbel statistical distribution and it has the form (Sokáč et al, 2019):…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Because of this, we used in our research also alternative formulation of the onedimensional analytic solution of the ADE based on the assumption of asymmetrical substance spreading. This alternative solution is based on the Gumbel statistical distribution and it has the form (Sokáč et al, 2019):…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For this reason, an alternative function based on the asymmetrical substance spreading assumption has been used for the 1-D analytic solution of the ADE. This function comes from the Gumbel statistical distribution [32]:…”
mentioning
confidence: 99%
“…Even better results and conformity between models and data from real conditions can be obtained using the three parametric Generalised Extreme Value (GEV) distribution model [32]:…”
mentioning
confidence: 99%
“…The second review paper [11] deals with the environmental impacts associated with the rapidly growing mariculture industry, while one research paper [12] investigated the flow and concentration patterns downstream an aquaculture cage net panel in parametric flume experiments. Four studies approached the stream and river systems from a variety of perspectives, ranging from the physical modelling of flow with vegetation [13] and the numerical simulation of solute transport in river with dead zones [14], to the laboratory study of flood discharge atomisation [15] and the geomorphic characterisation and classification of a large river [16]. Three contributions are about hyporheic fluxes: two field studies investigated these fluxes at a small river confluence [17] and the effects of such fluxes on the macroinvertebrate community [18], while their relationship with the bioturbation activity of macroinvertebrates was studied in laboratory [19].…”
mentioning
confidence: 99%
“…However, natural streams often contain complexities such as transient storage zones (dead zones), vegetation and irregular stream morphology that could interfere with the solute transport processes, causing a strong asymmetry in the shape of the concentration distribution curve over time and invalidating the Gaussian distribution traditionally assumed in classic 1D ADE. To address this issue, Sokáč et al [14] proposed a simple 1D model with alternative asymmetrical statistical distributions, such as Gumbel, log-normal and generalised extreme value (GEV), for solute transport in streams with dead zones. Tests against literature field tracer experiments as well as data collected in three small streams in Slovakia with dead zones suggested that, compared with Gaussian distribution, the alternative formulations overall showed a significantly improved prediction of the dispersion process from an instantaneous source.…”
mentioning
confidence: 99%